RLX-2 ameliorates post-traumatic joint contracture by inhibiting the cGAS-STING signaling pathway - Jian-Jun Chen; Quan-Bing Zhang; Yan Wang; Chen Chen; Yi Liu; Zun-Yu Du; Xiu-Li Kan; Han Xiao; Xue-Ming Li; Run Zhang; De-Ting Zhu; Xian-Liang Rao; et al. (Tissue and Cell, 2027)

The unintentional adverse effect of Fe3 + on trimethoprim adsorption at environmentally relevant concentration by extracellular polymeric substances - You Ma; Tian-Yu Li; Zi-Yi Fan; Han Meng; Guo-Xiang Wang; Fang Fang; Yu-Dong Chen; Run-Ze Xu; Wen-Ming Xie (Journal of Environmental Chemical Engineering, 2026)

Synergistic stabilization of a clean-label bigel: whey protein isolate constructing dual oleogel/hydrogel networks - Run-Hao Fu; Han Tao; Bao-Cai Xu; Ran Feng; Bao Zhang (Food Hydrocolloids, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Structural features of endogenous polyphenols in modulating oxidative stability of tiger nut (Cyperus esculentus L.) oil: Insights from Rancimat and density functional theory - Zheng-Kai Zhang; Meng-Chen Xie; Jun-Chao Zhang; Lu-Han Sun; Xiao-Shuang Cai; Run-Yang Zhang; Guo-Qiang Zhang; Hua-Min Liu (Food Chemistry, 2026)

Asymmetric microbial community reassembly under 7-year experimental precipitation decouples soil carbon storage in a coastal wetland - Run Dang; Leilei Xiao; Lifeng Zhou; Jian Liu; Zhenghao Liang; Yan Wang; Weimin Song; Xiaojie Wang; Xiaojing Chu; Xiaoshuai Zhang; Yang Song; Wanlin Song; et al. (Environmental Research, 2026)

Experimental and numerical investigation into the interfacial performance of Fe-SMA strips bonded to cold-formed steel C-section substrates - Hai-Tao Wang; Wen Su; Han-Ying Qi; Zhiqiang Dong; Xinliang Sun; Run-Ze Zhu (Engineering Structures, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Microbial Decomposition of Lignin to Methane Reduces Net Blue Carbon Benefit Across China's Saltmarshes - Leilei Xiao; Chuancheng Fu; Isaac R. Santos; Carlos M. Duarte; Jian Liu; Lifeng Zhou; Meng Zhou; Run Dang; Jinkuo Lin; Kai Xiao; Yongming Luo; Guangxuan Han (Global Change Biology, 2026)
CH 4 emissions from mangrove, saltmarsh, and seagrass ecosystems partially offset carbon sequestration, potentially diminishing the climate mitigation capacity of these blue carbon habitats. However, a mechanistic understanding of the processes governing CH 4 production potential across large spatial scales remains limited. By integrating incubation‐based measurements from 116 sites, we reveal significant ecosystem‐specific differences in CH 4 production potential, with saltmarshes emerging as CH 4 production hotspot relative to mangroves and seagrass meadows. Using an integrated analytical approach encompassing more than 30 environmental, biogeochemical, and microbial parameters, we demonstrate that CH 4 production potential converges on sediment organic carbon availability, particularly plant‐derived carbon, as a key regulatory axis. Additionally, metagenome‐assembled genomes (MAGs) recovered from saltmarshes show a functional bias toward lignin degradation, thereby fueling downstream CH 4 production via methylotrophic pathways. Lignin‐addition and stable carbon isotope experiments further provide supportive evidence that lignin decomposition enhances Chinese saltmarsh CH 4 production potential, revealing a pathway that may reduce net blue carbon benefit. Together, these findings underscore that saltmarsh plant‐derived lignin is less stable than conventionally assumed, as microbial processing redirects stored carbon toward CH 4 production, challenging current blue carbon accounting frameworks at a continental scale within China.

Characteristics of the radar bright band observed over a high-altitude lake - Run Han; Yingying Chen; Xiaoyan Ling; Kun Yang; Xin Li; Junbo Wang; Changhui Zhan; Xu Zhou; Ming Chen (Atmospheric Research, 2026)

Pleurotus citrinopileatus polysaccharide inhibits glioma growth by downregulating the expression of CHI3L1--- CHI3L1 as a therapeutic target in glioma - Nuo-Ling Ye; Bing-Bo Zhuang; Hao-Dong Chen; Run-Qi Zou; Gang-Feng Cai; Jin-Hai Huang; Han Meng; Chun-Hua Wang; Jing Chen (Food and Bioproducts Processing, 2026)

From species to therapeutic property: distribution differences of threatened Chinese medicinal plants under climate change - Yun-Han Chen; Rui Yang; Run-Han Jiang; Yu Xia; Ling-Feng Mao (Biodiversity and Conservation, 2026)

Multifunctional microbial desalination cell for industrial wastewater treatment: Synergistic pyridine degradation, nitrogen removal and desalination - Ying Guan; Run Liu; Yuanbo Zhou; Hongwei Zhu; Siqi Tong; Yi Wang; Kajia Wei; Weiqing Han (Journal of Environmental Chemical Engineering, 2026)

Coordinated EISCAT and all-sky imager observations of dayside aurora effects on polar cap patch vertical properties - Zhiwei Wang; Desheng Han; Huixuan Qiu; Yong Wang; Huigen Yang; Jian Zhang; Jianjun Liu; Xiangcai Chen; Qiang Zhang; Su Zhou; Run Shi (Science China Earth Sciences, 2026)

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Observational evidence of ionospheric feedback effect in generating throat aurora - Huixuan Qiu; Desheng Han; Yong Wang; Qiang Zhang; Huiting Feng; Run Shi; Shunrong Zhang; Zhiwei Wang; Yongliang Zhang (Science China Earth Sciences, 2026)

Research on Intelligent Identification of Dike Hidden Hazards Based on GprMax Forward Modeling and YOLOv11 Deep Learning: A Case Study of Wenzaobang River in Shanghai - Fu-yu Jiang; Run Han; Li-kun Gao; Jiong Ni; Jun-kai Yu; Xiao-yu Xu (Applied Geophysics, 2026)

Mitigation of adverse effects of calcium on struvite biomineralization for phosphorus recovery - Xingtong Chen; Yongyun Li; Yifei Ma; Bing Li; Yihe Qin; Xiaoman Li; Run Yuan; Jingjing Chen; Suran Huang; Han Li; Haiming Huang (Bioresource Technology, 2026)

Fluid migration in calcite nanopores under salinity gradients: Insights from molecular dynamics - Yi Chen; Yan Zhang; Run-Sheng Han; Lei Wang (Acta Geochimica, 2026)

Biomass growth, nutrient removal, and microbial community dynamics in mono-, Co-, and sequential culture of screened cyanobacteria with microalgae for dairy wastewater treatment - Khin Khin Phyu; Suli Zhi; Junfeng Liang; Zengjun Yang; Run Zhao; Jiahua Liu; Yuang Cao; Han Wang; Keqiang Zhang (Bioresource Technology, 2026)

High-precision geochronology of the Early Cretaceous Jiufotang Formation: Temporal constraints on the late phase of the Jehol Biota - Yu-Ting Zhong; Magdalena H. Huyskens; Run-Jian Chu; Han-Qing Yang; Jian-Fang Hu; Ya-Qiong Wang; Shi-Xi Cai; Qiong Wu; Qiang Ma; Huai-Chun Wu; Qing-Zhu Yin; Yi-Gang Xu (Earth and Planetary Science Letters, 2025)

Scalable production of Actinidia arguta adventitious roots in air-lift bioreactors and their antibacterial efficacy against Staphylococcus aureus - Wen Jiang; Xue-Han Zong; Song-Hao An; Jing-Run Xiu; Shuo Yu; Ke-Xin Zhang; Yue-Jun Hao; Mei-Yu Jin (In Vitro Cellular & Developmental Biology - Plant, 2025)

Finite-time output feedback control of unmanned marine surface vessels with rotatable thrusters and propellers under deception attacks in an IoT environment - Xiangfei Meng; Guichen Zhang; Bing Han; Yanji Liu; Mengwei Chen; Run Lu (Ocean Engineering, 2025)

Water quality analysis of organic pollutants in electronic industry manufacturing wastewater based on spectral analysis and molecular level exploration - Run Yuan; Yihe Qin; Han Li; Weiqing Huang; Haiming Huang; Xuwen He (Journal of Water Process Engineering, 2025)

Exploration of extracellular polymeric substances changes and related antibiotic resistance gene migration and transformation patterns in microalgae under lead stress and gibberellin stimulation - Xiaoyu Xu; Yuang Cao; Suli Zhi; Cheryl Marie Cordeiro; Erik Sindhøj; Khinkhin Phyu; Han Wang; Jiahua Liu; Keqiang Zhang; Run Zhao (Journal of Hazardous Materials, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

Microbial mineralization of struvite by using talc and its implications for phosphorus recovery - Xingtong Chen; Tianlei Zhao; Bing Li; Yihe Qin; Xiaoman Li; Run Yuan; Jingjing Chen; Han Li; Haiming Huang (Applied Clay Science, 2025)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

Naked mole-rat-derived high molecular weight hyaluronic acid protects against DSS-induced intestinal inflammation - Shuyin Wu; Lei Xing; Xiaolong Wu; Run Quan; Keyi Du; Jianchun Han; Huili Tong; Shuai Shi (Food Bioscience, 2025)

Terrestrial–aquatic microbial community coalescence slows litter decomposition in forest streams - Han Jiang; Yinghui Yang; Jiawen Liang; Run Liu; Yueting Pan; Tingting Cao; Siyuan Chen; Zunian Ran; Chang Zhao; Yanli Tian; Xingjun Tian (Plant and Soil, 2025)

Current perspectives on microalgae and extracellular polymers for reducing antibiotic resistance genes in livestock wastewater - Xiaoyu Xu; Yuang Cao; Suli Zhi; Khinkhin Phyu; Han Wang; Jiahua Liu; Cheryl Marie Cordeiro; Erik Sindhøj; Keqiang Zhang; Run Zhao (Bioresource Technology, 2025)

Bioinspired hydrogel tactile sensor via pressure-intensified ion signals with self-healing and anti-frozen capability - Yi-Han Xue; Tian-Run Lv; Huiting Zhang; Ya-Qiong Yang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2025)

Rational metabolic engineering of Escherichia coli for the industrial-scale production of l-phenylalanine - Minliang Chen; Chao Han; Peng Zhou; Run Shi; Zhiwei Xing; Qianqian Chen; Gou-an Xie; Rufei Xie; Wei Tan; Hengyu Liang (Bioresource Technology, 2025)

Effects of alternating wet and dry irrigation regimes on rice growth and physiology characteristics in southeast China - Rui Zhou; Haofang Yan; Chuan Zhang; Xingye Zhu; Guoqing Wang; Bin He; Kinda Negessa Disasa; Imran Ali Lakhiar; Run Xue; Yudong Zhou; Biyu Wang; Jun Li; et al. (Paddy and Water Environment, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Microbiota-induced asymmetry in coastal methane emission potential under experimental precipitation gradients - Lifeng Zhou; Lirong Zhang; Run Dang; Guangxuan Han; Jian Liu; Meng Zhou; Leilei Xiao (Environmental Research, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Tri-functional molecular junction photocatalyst for cascade synthesis of N-benzylideneaniline derivatives - Xiao-Xin Li; Xiao-Xuan Hong; Zi-Yi Liao; Lei Zhang; Run-Han Li; Ying Zeng; Yue Liu; Shun-Li Li; Ya-Qian Lan (Science Bulletin, 2024)

Synchrotron-based P K-edge XANES spectroscopy reveals the transition of phosphorus cycling in the early Cambrian ocean - Pengcheng Ju; Zhenfei Wang; Chao Chang; Zhangqin Zheng; Run Li; Wenpeng Xia; Xuyang Cao; Yigui Han; Mingyu Zhao; Chao Li; Xingliang Zhang; Kang-Jun Huang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Sustainable utilization of phosphorus-rich sludge in cement composites: Multiscale evaluation and mechanistic analysis - Shengli Ren; Zhirong Xu; Benqin Yang; Xiao-Yong Wang; Yi Han; Run-Sheng Lin; Yongpang Liao (Journal of Environmental Chemical Engineering, 2024)

Study on the thermo-hydraulic behaviors within a CiADS 61-pin wire-wrapped fuel assembly under porous blockage conditions based on LBEblockageFoam - Yun-Xiang Li; Run-Sheng Yang; Yue Li; Xing-Kang Su; Yi-Wen Han; Zi-Nan Huang; Lu Meng; Song Li; You-Peng Zhang; Lu Zhang; Wei Jiang (Annals of Nuclear Energy, 2024)

Resistivity tomography based on multichannel electrodes - Fu-yu Jiang; Jiong Ni; Hai-jun Chen; Li-kun Gao; Song Chen; Xian-wei Wu; Zhi-qiang Su; Yao Lei; Ming-hui Dai; Run Han; Jun-kai Yu (Applied Geophysics, 2024)

Hydrophobic surface modification and morphology tuning of supported KNiMoS-based catalyst for synergistically enhanced higher alcohols synthesis via CO hydrogenation - Yihua Cao; Xueli Yin; Run Cai; Xinyi Han; Yindan Wu; Likun Wen; Yichen Song; Xiaoping Dai (Chemical Engineering Journal, 2024)

Effect of Voluntary Wheel Running on Anxiety- and Depression-Like Behaviors in Fluoride-Exposed Mice - Mengjie Qi; Yue Wu; Han Shi; Jie Liu; Run Zhu; Jixiang Wang; Amna Rafique; Bo Yang; Ruiyan Niu; Ding Zhang; Zilong Sun (Biological Trace Element Research, 2024)

Dual-Functional group passivation to foster buried interface Cohesion for High-Performance perovskite photovoltaics - Namatullah Nizamani; Kai-Li Wang; Run-Jun Jin; Chun-Hao Chen; Jing Chen; Yu Xia; Lei Huang; Yu-Han Li; Mary Donnabelle Balela; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2024)

Ecotoxicological assessment, oxidative response, and enzyme activity disorder of the rotifer Brachionus asplanchnoidis exposed to a toxic cocktail of spent lithium-ion battery leachate - Yi-fan Feng; Yu Zhang; Run-jia Yang; Si-qi Li; Xiao-jie Liu; Cui Han; Yi-fu Xing; Jia-xin Yang (Journal of Hazardous Materials, 2024)

A novel wireless IoT sensing system for cable force identification and monitoring - Pinghe Ni; Run Zhou; Qiang Han; Xiuli Du; Kun Xu; Zhenlei Jia; Yulei Bai (Engineering Structures, 2024)

3D printed micro-structured hydrogel device with transmittance-changeable soft ‘armor’ camouflage for dual-encryption - Jia-Yue Zhang; Tian-Run Lv; Yi-Han Xue; Wen-Hai Zhang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2024)

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

A novel stress concentration inspection method for marine oil and gas pipeline based on UNSM - Jiaxing Xin; Jinzhong Chen; Renyang He; Rui Li; Xiaolong Li; Chang Liu; Run-kun Lu; Zhengda Su; Wenbo Han (Ocean Engineering, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Effects of extraction methods on the structure and functional properties of soluble dietary fiber from blue honeysuckle (Lonicera caerulea L.) berry - Run Ji; Xiuling Zhang; Chenghai Liu; Wentao Zhang; Xiaofeng Han; Hengtian Zhao (Food Chemistry, 2024)

Methyl-functionalized Zn-MOF for selective adsorption and separation of acetylene - Zi-Han Wang; Run-Han Su; Gang-Ding Wang; Wen-Juan Shi; Lei Hou (Journal of Environmental Chemical Engineering, 2023)

Role of Mutations of Mitochondrial Aminoacyl-tRNA Synthetases Genes on Epileptogenesis - Ling-yue Kong; Yi-ze Wu; Run-qi Cheng; Pei-han Wang; Bi-wen Peng (Molecular Neurobiology, 2023)

Continuous Co-incorporation of Chinese Milk Vetch and Rice Straw with Reduced Chemical Fertilizer Maintains Rice Yield as a Consequence of Increased Carbon and Nitrogen Storage in Soil Aggregates - Rongyan Bu; Wenlong Cheng; Shang Han; Run Hu; Hui Wang; Shan Tang; Min Li; Qin Zhu; Ji Wu; Weidong Cao (Journal of Soil Science and Plant Nutrition, 2023)

Soot formation in high-pressure combustion: Status and challenges - Huaqiang Chu; Jiawei Qi; Shunjie Feng; Wenlong Dong; Run Hong; Bingbing Qiu; Weiwei Han (Fuel, 2023)

Effect of polylactic acid microplastics on soil properties, soil microbials and plant growth - Run Liu; Jiawen Liang; Yinghui Yang; Han Jiang; Xingjun Tian (Chemosphere, 2023)

Measurement of water resources carrying capacity in Gugang Town of Central China based on human-water-agriculture framework - Si Chen; Xuexing Zhu; Yunchen Zhou; Yunan Yan; Run Wang; Peng Han (Science of The Total Environment, 2023)

Eliminating temporal correlation in quantum-dot entangled photon source by quantum interference - Run-Ze Liu; Yu-Kun Qiao; Han-Sen Zhong; Zhen-Xuan Ge; Hui Wang; Tung-Hsun Chung; Chao-Yang Lu; Yong-Heng Huo; Jian-Wei Pan (Science Bulletin, 2023)

Diversity of sesquiterpenoids from Stellera chamaejasme with neuroprotective effects - Fang-Yu Yuan; Zhuo-Ya Tang; Xue-Long Yan; Dong Huang; Han-Zhuang Weng; Jia-Luo Huang; Run-Zhu Fan; Ye Chen; Sheng Yin; Gui-Hua Tang (Phytochemistry, 2023)

The decreased expression of GW2 homologous genes contributed to the increased grain width and thousand‑grain weight in wheat-Dasypyrum villosum 6VS·6DL translocation lines - Zhiyu Feng; Long Song; Wanjun Song; Zhongqi Qi; Jun Yuan; Run Li; Haiming Han; Huifang Wang; Zhaoyan Chen; Weilong Guo; Mingming Xin; Jie Liu; et al. (Theoretical and Applied Genetics, 2021)

Identification and functional characterization of a PDR transporter in Tripterygium wilfordii Hook.f. that mediates the efflux of triptolide - Guopeng Miao; Juan Han; Yan-bo Huo; Cheng-run Wang; Shun-chang Wang (Plant Molecular Biology, 2021)

Insight into the Dissolution Molecular Mechanism of Ternary Solid Dispersions by Combined Experiments and Molecular Simulations - Run Han; Tianhe Huang; Xinyang Liu; Xunqing Yin; Haifeng Li; Jiahong Lu; Yuanhui Ji; Huimin Sun; Defang Ouyang (AAPS PharmSciTech, 2019)

Analysis of genetic variation of porcine circovirus type 2 within pig populations in central China - Peng-Li Xu; Yu Zhao; Hui-Hua Zheng; Run-Bo Tian; Hao-Ying Han; Hong-Ying Chen; Lan-Lan Zheng (Archives of Virology, 2019)

Structural Changes, Volatile Compounds and Antioxidant Activities of Maillard Reaction Products Derived from Scallop ( Patinopecten yessoensis ) Female Gonad Hydrolysates - Jia-Run Han; Yi-Nan Du; Yue Tang; Jun Zhao; Wen-Hui Shang; Jia-Nan Yan; Hai-Tao Wu; Bei-Wei Zhu (Journal of Aquatic Food Product Technology, 2019)

Protection of melon against Fusarium wilt-root knot nematode complex by endophytic fungi Penicillium brefeldianum HS-1 - Guo-peng Miao; Juan Han; Ke-gui Zhang; Shun-chang Wang; Cheng-run Wang (Symbiosis, 2019)

Rheological Behavior of Protein Hydrolysates from Papain-treated Male Gonad of Scallop ( Patinopecten yessoensis ) - Jia-Run Han; Jia-Nan Yan; Yi Li; Jun Zhao; Yue Tang; Wen-Gang Jin; Wen-Hui Shang; Meng Zhang; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2018)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Skarn mineralogy and its geological significance for the Tayuan (Cu–Mo)–Pb–Zn deposit, northern Daxinganling metallogenic belt - Chao Li; Tao Ren; Jian-Guo Huang; Run-Sheng Han; He-Jun Yin; Hong-Yang Zhou; Zhi-Hong Feng (Acta Geochimica, 2017)

Between-subject variability: should high be the new normal? - Hesham S. Al-Sallami; Song Lim Cheah; Shiou Yii Han; Joel Liew; Jin Lim; Mary Anne Ng; Hayneil Solanki; Run Jie Soo; Victoria Tan; Stephen B. Duffull (European Journal of Clinical Pharmacology, 2014)

Evaluation of allowable withdrawn volume of groundwater based on observed data - Ye-Shuang Xu; Run-Qiu Huang; Jie Han; Shui-Long Shen (Natural Hazards, 2013)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Different expression patterns of CK2 subunits in the brains of experimental animals and patients with transmissible spongiform encephalopathies - Jian-Ming Chen; Chen Gao; Qi Shi; Bing Shan; Yan-Jun Lei; Chen-Fang Dong; Run An; Gui-Rong Wang; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Archives of Virology, 2008)